STUDI AGRIBISNIS TANAMAN TALAS BOGOR DI DESA TAMAN SARI KECAMATAN TAMAN SARI KABUPATEN BOGOR JAWA BARAT - Priyadi, Eldi; Abubakar, Rafeah; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2014)
This study aims to determine how agribusiness Bogor taro plant in the village of Taman Sari Taman Sari subdistrict, Bogor Regency of West Java. And to find out how much taro farm income Bogor sub-district in the village of Taman Sari Taman Sari Bogor West Java. This research was conducted by taking primary data on taro plants agribusiness Bogor village of Taman Sari Taman Sari subdistrict, Bogor regency of West Java that was conducted in December 2013 through January 2014 The purpose of this study was to determine how the taro crop agribusiness Bogor Park Village Sari Taman Sari subdistrict, Bogor regency of West Java. And to find out how much taro farm income Bogor sub-district in the village of Taman Sari Taman Sari Bogor West Java. The research method used in this study is the survey method. This method is the investigation conducted to obtain the facts of the existing symptoms and seek factual particulars, both on social institutions, economics or politics of a group or a region. The results of this study indicate that the taro plant Agribusiness conducted by taro farmers include: Subsystem provision of means of production, farming Subsystem and Subsystem marketing. Taro plant sales activities conducted by taro farmers is by way of sale to Bogor and Taman Sari market the way consumers come directly to localized business, and the income derived from farming taro farmers per cropping season is Rp. 11.507.656,26.